Composition and diversity of soil bacterial communities under identical vegetation along an elevational gradient in Changbai Mountains, China - Li, Mengsha; Dai, Guanhua; Mu, Liqiang (Frontiers in Microbiology, 2022)
Soil bacteria play important roles in biogeochemical cycling and biodiversity in mountain ecosystems. Past studies have investigated the bacterial community composition and diversity in elevation gradations covered by different vegetation types, but for a better assessment of elevation effects, here we studied bacterial communities in soil under identical vegetation cover. High-throughput amplicon sequencing of the V3-V4 region of bacterial 16S rDNA was used to investigate the diversity and composition bacterial communities in soil from 700 to 1000 m above sea level collected on the north slope of Changbai Mountains, Northeast China. Differences in soil physicochemical parameters were observed at different elevations. Soil bacterial abundance indices (Richness, Chao1, ACE) differed significantly along the elevation gradient, whereas the Shannon index remained unchanged. Principal Coordinates Analysis indicated separated soil bacterial communities of the different elevations. The dominant phyla in all soil samples were Proteobacteria, Acidobacteria, Actinobacteria, Verrucomicrobia, and Bacteroidetes, which in combination reached 80–85%. Soil pH to some extend related to soil bacterial community along altitude gradations. The relative abundance of a multiple phyla was negatively affected by the soil nutrients ammonium, nitrate, available P, soil moisture content, and soil organic C. The strongest effects were seen for Proteobacteria. The pH either positively or negatively correlated with specific genera. Overall, the changes in soil physicochemical properties with elevation are important in shaping the bacterial diversity and composition in soil with the same above-ground vegetation of Changbai Mountains.